(untitled) (Revista Iberoamericana de Bioética, 2018)
Public health communication and, especially during a crisis scenario such as an epidemics, is mediated by ethical conflicts ranging from values to deontology. In an intercommunicated world, the social support during outbreaks and epidemics becomes global and the state presence is a key to social protection. This should also be translated into timely, urgent and effective communication strategies from the public health perspective as well as efforts to prevent and avoid fake news or skewed information from any sources. Scenarios with lack of connection and obstacles in mass communication in public health major threats are described.